The Effect of Cooperative Learning Model Using Animation and Motivation to Improve Student Learning Outcomes in Geometric Optics Material In Grade XI Of Senior High School Negeri 3 Medan Academic Year 2025/2026 - Pinondang Hutapea; Marice Hotnauli Simbolon (Cattleya Darmaya Fortuna, 2026)
The aims of this study were: There were differences in physics learning outcomes of students who were taught using cooperative learning models using animation comp ared to cooperative learning without using animation. There are differences in learning achievement in groups of students who have high motivation and groups of students who have low motivation. Interaction between cooperative learning using animation media with motivation in increasing learning outcomes. This research is quasi-experimental. The research population was students of class XI Science at High School Negeri 3 Medan Negeri Academic Year 2025/2026. The sampling technique used a purposive sample consisting of two classes with a total sample of 72 students. The research instruments are learning achievement tests and student learning motivation questionnaires. The test used to obtain data is in the form of multiple choice. The data in the study were analyzed using SPSS 25 with two-way ANOVA. The results of the ANOVA test obtained: The physics learning achievement of students who were taught by the cooperative learning model using animation media was higher than the physics learning outcomes of students who were taught by the learning model cooperative without using animation media. The physics learning achievement of students who have high motivation is higher than the physics learning outcomes of students who have low motivation. There is an interaction between cooperative learning models using animation media and motivation in improving learning outcomes.